SOCIAL NETWORKS AS A TOOL FOR DIGITAL MARKETING IN BANKING IN SERBIAA - Nikolić, Milena; Marković Blagojević, Marija; Milojković, Danka (The European Journal of Applied Economics, 2025)
Due to rapid IT technology development, many people and enterprises are now active users of social networks. Traditional banking communication channels have become insufficient to meet the demands of modern business conditions. To adapt to the evolving preferences of existing and potential clients in an increasingly competitive market, banks have had to embrace digital technologies and redefine their business strategies, customer engagement, and communication approaches. Digital changes have given clients a distinctive experience and strengthened the banks’ position in the financial market. Today, banks are increasingly present on social networks across the world, including Serbia. The presence of banks in Serbia on social networks was analysed in the paper following analytical-synthetic, hypothetical-deductive, desk research, content analysis, and comparative methods. The research results showed that 80% of banks use at least three social networks and that the use of Instagram, YouTube, Facebook, and LinkedIn in promotion is increasingly common in the banking sector in Serbia. Banks that have not yet established a presence on these networks should consider their implementation to strengthen the brand, engage younger and business users, and expand the business network.
Keywords: social networks, banks, financial services, digital marketing, digital communication channels